PENGARUH PENDIDIKAN DAN PELATIHAN (DIKLAT) TERHADAP PENINGKATAN KINERJA TENAGA PENYULUH PERTANIAN PADA BADAN PELAKSANA PENYULUHAN PERTANIAN, PERIKANAN, DAN KEHUTANAN (BP4K) KABUPATEN TOBA SAMOSIR - Melisa Simanjuntak; Harapan Tua (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
The Toba Samosir Extension Executive Agency of Agriculture, Fisheries and Forestry is one of the government agencies that have a principal function of the increasing extension in agriculture , fisheries and forestry are reflected in agriculture , fisheries and forestry to stabilization of staple food prices and the economic capacity of managing public peasants in the countryside.The purpose of this study was to determine and analyze the influence of Education and Training (Training ) to increase performance in Agricultural Extension in the implementing Agriculture at extension, agency Fisheries and Forestry ( BP4K ) Toba Samosir . The population of this research is all the Agricultural Extension Extension Executive Agency of Agriculture, Fisheries and Forestry Toba Samosir , as many as 59 people . Technics research sample is census , where all members of the population used as a sample , then the entire population in this study serve as a member of the sample . Required data , collected through observation and questionnaires . The data analysis technique used is a simple linear regression analysis.The results of this study indicate that the Education and Training (Training ) has a significant impact on performance improvement extension. This proved by test determination coefisient with a value R2 of (0.935), the influence of Education and Training (Training ) on the performance of 93% extension . While the remaining 7 % influenced of other factors.Advice given as an insert to the Executive Agency Counseling agencies Agriculture, Fisheries and Forestry on the Toba Samosir for more attention to employee development through training assignments to achieve improved performance expected by the agency . Should Head should be better in attention to things that can affect the performance improvements that increase agricultural productivity , because based on the research conducted there were 7 % more other factors that can affect the performance of extension .Keywords : Education and Training and Performance